Silicon-based negative electrode material and preparation method and application thereof
By co-doping silicon oxide deposits with carbon matrix and sodium magnesium in the silicon-based anode material to form a silicon-based anode material with a core-shell structure, the problem of low efficiency of silicon-based anode materials in the prior art was solved, and the expansion performance and cycle stability of the material were significantly improved.
Patent Information
- Application Number
- CN202411843042.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing silicon-based anode materials have shortcomings in the first Coulomb efficiency, resulting in poor expansion performance and cycle stability of the material when used in lithium-ion batteries.
A carbon matrix is used as the matrix and filled with sodium-magnesium co-doped silicon oxide deposits to form a silicon-based negative electrode material with a core-shell structure. The homogeneous magnesium-doped sub-silicon oxide core improves first-time Coulomb efficiency, while the sodium sickle-co-doped sub-silicon oxide shell forms a loose stacking structure, reducing the risk of material expansion and powderization.
The first Coulomb efficiency of silicon-based anode material is significantly improved, the expansion performance and cycle stability of the material are improved, making it more suitable as an anode material for lithium-ion batteries.
Smart Images

Figure CN119852350A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery electrode materials, and in particular to a silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] Silicon-based anode materials are widely considered to be an ideal replacement for graphite anodes due to their ultra-high theoretical specific capacity (4200mAh / g, 10 times that of graphite anodes), lower voltage platform (~0.4Vvs.Li / Li+) and abundant reserves in nature. However, silicon-based materials also have problems such as large volume changes during lithium extraction / insertion, resulting in stripping from conductive agents and binders, and unstable SEI formed after particle crushing, which limits their commercialization.
[0003] In view of the above problems, the prior art such as CN115621433A, CN118198291A and other patents disclose that silicon-based negative electrode materials prepared by depositing silicon oxide materials in porous matrix materials provide structural support and reserve volume expansion buffer space when silicon is embedded with lithium, so that the prepared silicon-based negative electrode materials have excellent rate performance and expansion performance. However, silicon oxide itself has the problem of low first coulomb efficiency. After being deposited into the porous matrix, the first coulomb efficiency of the material will also be poor, which is difficult to meet the requirements of practical applications. Summary of the invention
[0004] The present invention provides a silicon-based negative electrode material and a preparation method and application thereof, so as to solve the technical problem of poor first coulombic efficiency of the existing estimated negative electrode material mentioned in the background technology.
[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A silicon-based negative electrode material comprises a carbon matrix and sodium-magnesium co-doped silicon oxide deposits filled in the pores of the carbon matrix; the silicon oxide deposits present a core-shell structure, comprising a silicon oxide core uniformly doped with magnesium and a sodium-magnesium co-doped silicon oxide shell, wherein the doping amount of the sodium element in the sodium-magnesium co-doped silicon oxide shell gradually decreases from the outside to the inside.
[0006] The design idea of the above technical solution is that silicon oxide is deposited in the silicon-based negative electrode material of the present invention, and the deposited silicon oxide is different from the prior art and has a core and an outer shell. The core is silicon oxide doped uniformly with magnesium, and the outer shell is sodium-magnesium co-doped silicon oxide in which the sodium ion concentration gradually decreases from the outside to the inside. The uniformly magnesium-doped silicon oxide core can significantly improve the first coulombic efficiency of the silicon-based negative electrode material, and solve the problem of the decrease in the first efficiency of the material caused by the simple deposition of silicon oxide in the prior art. At the same time, the sodium-magnesium co-doped silicon oxide shell can form a loose stacking structure, which is convenient for the insertion and removal of lithium ions, and can also further reduce the expansion of the material, reduce the risk of pulverization and cracking of the material during lithiation and delithiation, and improve the expansion performance and cycle stability of the material.
[0007] As a further preferred embodiment of the above technical solution, the sodium-magnesium co-doped silicon oxide deposit accounts for 25% to 70% of the mass of the silicon-based negative electrode material; the doping amount of the magnesium element is 1% to 30% of the mass of the sodium-magnesium co-doped silicon oxide deposit, and the doping amount of the sodium element is 0.2% to 6.5% of the mass of the silicon-based negative electrode material. As a further preferred embodiment of the above technical solution, the silicon-based negative electrode material is coated with a carbon coating layer, and the thickness of the carbon coating layer is 1 to 150 nm, and more preferably 5 to 20 nm. The carbon coating layer can further reduce interface side reactions and improve the cycle stability of the material.
[0008] As a further preferred embodiment of the above technical solution, the carbon matrix is porous carbon, and the particle size D50 of the porous carbon is 1-25 μm, and the pore volume is 0.6-1.2 cm 3 / g, and the specific surface area is 1600~2200 m 2 / g.
[0009] Based on the same technical concept, the present invention also provides a method for preparing the silicon-based negative electrode material described in the above technical solution, comprising the following steps: (1) mixing silicon powder, silicon dioxide powder and magnesium powder to obtain a mixed powder; (2) placing the mixed powder in a reaction zone of a vacuum sintering furnace, placing carbon powder in a receiving zone of the vacuum sintering furnace, and heating the vacuum sintering furnace to deposit the mixed powder in the carbon powder to obtain an intermediate product; (3) The intermediate product is mixed with sodium salt to obtain a mixture, the mixture is placed in a reaction furnace, and reacted at 550-1000° C. for 2-20 hours under a protective atmosphere, and then a carbon source gas is introduced to continue the reaction for 2-5 hours to obtain the silicon-based negative electrode material.
[0010] The design idea of the above technical solution is that the present invention uses porous carbon as the matrix material, and deposits uniformly magnesium-doped silicon oxide into the substrate, thereby further improving the first coulomb efficiency of the silicon-based composite material. At the same time, the outer layer of the silicon oxide deposit is treated with sodium-magnesium co-doping. Due to the presence of porous carbon, the decomposition of sodium salt can be promoted to achieve an unbalanced arrangement of O-Na and O-Mg bonds, with a longer O-Na bond length and a loose structure; and a shorter O-Mg bond length and a dense structure. In the Li-NaMg-SiO system, the binary doping source will cause unbalanced repulsion, thereby forming a loose stacking structure in the outer layer of the deposit, which can facilitate the insertion and removal of lithium ions and improve the expansion performance and cycle stability of the material.
[0011] As a further preferred embodiment of the above technical solution, in step (2), the mass ratio of the mixed powder to the carbon powder is 1:(0.4-3.0).
[0012] As a further preferred embodiment of the above technical solution, in step (2), during the deposition process, the temperature of the reaction zone of the vacuum sintering furnace is controlled at 1300-1700° C., the temperature of the transition zone is controlled at 1200-1450° C., and the temperature of the receiving zone is controlled at 700-900° C. By performing a three-stage gradient temperature control process on the sintering furnace, the influence of excessively high temperature heat radiation in the reaction zone on the material in the receiving zone can be avoided, which can effectively improve the material recovery rate.
[0013] As a further preferred embodiment of the above technical solution, in step (2), the carbon powder is porous carbon, and the particle size D50 of the porous carbon is 1-25 μm, and the pore volume is 0.6-1.2 cm 3 / g, with a specific surface area of 1600 - 2200 m 2 / g.
[0014] As a further preferred embodiment of the above technical solution, in step (1), the mass proportion of the magnesium powder in the mixed powder is 1% to 30%, and more preferably 3% to 20%. When the magnesium content is too low, the first coulombic efficiency of the material cannot be significantly improved. When the magnesium content is too high, the capacity of the synthetic material will be low.
[0015] As a further preferred embodiment of the above technical solution, in step (1), the molar ratio of silicon powder to silicon dioxide is (0.8-1.15): 1, and more preferably (1-1.10): 1. When the silicon ratio is too low, the material capacity and initial efficiency obtained by deposition will be low. When the silicon ratio is too high, more silicon will remain unreacted in the furnace, causing material loss.
[0016] As a further preferred embodiment of the above technical solution, in step (3), the mass proportion of the sodium salt in the mixture is 1% to 30%, and more preferably 1% to 20%.
[0017] As a further preferred embodiment of the above technical solution, in step (3), the sodium salt includes at least one of sodium carbonate, sodium bicarbonate and sodium acetate.
[0018] As a further preferred embodiment of the above technical solution, in step (3), the carbon source gas is acetylene, the protective atmosphere is a nitrogen atmosphere, and the mass flow ratio of nitrogen to acetylene is 1:(1-0.25).
[0019] Based on the same technical concept, the present invention also provides an application of the silicon-based negative electrode material described in the above technical solution or the silicon-based negative electrode material prepared by the preparation method described in the above technical solution in a lithium-ion battery.
[0020] The present invention has the following beneficial effects: (1) The silicon-based negative electrode material of the present invention solves the problem of decreased first efficiency of the material caused by the simple deposition of silicon dioxide in the prior art, has good first coulombic efficiency, low risk of material pulverization and cracking during lithiation and delithiation, good expansion performance and cycle stability, and can replace graphite negative electrode as the negative electrode material of lithium-ion batteries; (2) The method for preparing the silicon-based negative electrode material of the present invention has a simple process, is easy to operate, is highly compatible with the production equipment of the prior art, and can effectively improve the production efficiency and yield of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic structural diagram of the material receiving area of the vacuum sintering furnace of each embodiment.
[0022] Figure 2 Schematic diagram of the structure of the silicon-based negative electrode material of each embodiment.
[0023] Figure 3 This is the XRD diagram of the silicon-based negative electrode material of Example 1. DETAILED DESCRIPTION
[0024] The present invention will be described in detail below with reference to the accompanying drawings and embodiments, but the present invention can be implemented in many different ways as defined and covered by the claims.
[0025] Embodiment 1: like Figure 2 As shown, the silicon-based negative electrode material of this embodiment includes a porous carbon matrix (the particle size D50 of the porous carbon is 1-25 μm and the pore volume is 0.6-1.2 cm 3 / g, and the specific surface area is 1600~2200 m 2 / g) and sodium-magnesium co-doped silicon oxide deposits filled in the pores of the carbon matrix; the silicon oxide deposits present a core-shell structure, including a silicon oxide core uniformly doped with magnesium and a sodium-magnesium co-doped silicon oxide shell, in which the sodium doping amount of the sodium co-doped silicon oxide shell gradually decreases from the outside to the inside, and the magnesium element is uniformly distributed; the porous carbon matrix is coated with a carbon coating layer. The XRD pattern of the silicon-based negative electrode material of this embodiment is shown in FIG. Figure 3 As shown, it can be seen that the silicon-based negative electrode material of this embodiment also contains sodium magnesium silicate (such as Na2Mg5Si 12 O 30 etc.) and characteristic peaks of magnesium silicates (such as MgSiO3, etc.).
[0026] The silicon-based negative electrode material of this embodiment is prepared by the following method: (1) Silicon powder and silicon dioxide with a particle size of 3 to 5 μm were weighed and mixed at a molar ratio of 1.05:1, and magnesium powder was added to obtain a mixed powder; the mass proportion of magnesium powder in the mixed powder was 9%; (2) The mixed powder is placed in the reaction zone of a vacuum sintering furnace; the porous carbon (porous carbon D50 is 8.8 μm, specific surface area is 1890 m 2 / g, pore volume is 0.89 cm 3 / g) is placed in the vacuum sintering furnace receiving area 1 (structure as Figure 1 As shown in the figure, 1 is the material receiving area, 2 is the keel lining, and 3 is the stainless steel screen. The inner wall of the material receiving area is provided with a keel lining, and a stainless steel screen (such as Figure 1 As shown), the porous carbon is thinly spread on the stainless steel screen, and the thickness of the porous carbon is less than 3mm; the collecting area and the reaction area are connected. The mass ratio of the mixed powder to the porous carbon powder is 1:0.67, the vacuum reactor is heated, the sintering temperature of the reaction zone is controlled at 1380℃, the temperature of the transition zone is controlled at 1240℃, the temperature of the collecting zone is controlled at about 800℃, and the vacuum degree is controlled at 0.1~10Pa, so that the mixed powder is deposited in the carbon powder to obtain an intermediate product; (3) Sodium carbonate is mixed with the intermediate product to obtain a mixed material, wherein sodium carbonate accounts for 2% of the mass of the mixed material; the mixed material is placed in a reaction furnace, and reacted at 850°C for 5 h under the protection of a nitrogen atmosphere. After the reaction is completed, the furnace temperature is maintained, and acetylene carbon deposition is introduced for 3 h. The mass flow rate ratio of nitrogen to acetylene gas is 1:0.5. After the coating is completed, the silicon-based negative electrode material of this embodiment is obtained.
[0027] The silicon-based negative electrode material of this embodiment can be used to make lithium-ion batteries.
[0028] Embodiment 2: like Figure 2As shown, the silicon-based negative electrode material of this embodiment includes a porous carbon matrix (the particle size D50 of the porous carbon is 1-25 μm and the pore volume is 0.6-1.2 cm 3 / g, with a specific surface area of 1600 - 2200 m 2 / g) and sodium-magnesium co-doped silicon oxide deposits filled in the pores of the carbon matrix; the silicon oxide deposits have a core-shell structure, including a silicon oxide core uniformly doped with magnesium and a sodium-magnesium co-doped silicon oxide shell, in which the doping amount of the sodium element gradually decreases from the outside to the inside, and the magnesium element is uniformly distributed; the porous carbon matrix is coated with a carbon coating layer.
[0029] The method for preparing the silicon-based negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that the mass ratio of the mixed powder to the porous carbon powder in step (2) is 1:1.
[0030] Comparative Example 1: The preparation method of the silicon-based negative electrode material in this comparative example is basically the same as that in Example 1, except that the temperature of the reaction zone and the transition zone of the kiln used are both set to 1380°C.
[0031] Comparative Example 2: The preparation method of the silicon-based negative electrode material in this comparative example is basically the same as that in Example 1, except that sodium carbonate is not added in step (3).
[0032] Comparative Example 3: A silicon-based negative electrode material was prepared in the same manner as in Example 1, except that magnesium powder was not added in step (1).
[0033] The silicon-based negative electrode materials of each embodiment and comparative example were mixed with a conductive agent (Super-p) and a binder (LA133) at a mass ratio of 8:1:1 and water to prepare a slurry. The dispersed slurry was coated on a copper foil and dried, punched into an electrode sheet with a diameter of 16 mm, and then vacuum dried and assembled into a CR2032 button battery in a glove box: the prepared electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, and the electrolyte was 1 M LiPF6 (solvent: EC, DEC (volume ratio 1:1); solute: LiPF6; additive: 1% FEC, etc.). The prepared button battery was left to stand at room temperature for 24 h, and then subjected to constant current charge and discharge tests on the Blue Electric test system. The battery was activated with a current density of 0.1 C (designed according to 1C = 1500 mAh / g), and cycled for up to 50 cycles at a current density of 0.5 C. The charge and discharge cut-off voltage was 0.005~1.5 V, and the first cycle charge specific capacity, the first charge and discharge efficiency, and the capacity retention rate after 50 cycles were tested.
[0034] The deposition process recovery rate and full-charge expansion rate of the negative electrode sheets of the button cells made of the silicon-based negative electrode materials of the above embodiments and comparative examples were also tested. The specific testing process of the full-charge expansion rate is: the thickness D1 of the negative electrode sheet of the button cell made of the final material prepared in the embodiments and comparative examples after rolling is tested, and then the full-charge thickness D2 of the negative electrode sheet is disassembled when the button cell is fully charged to 100% SOC, and then the expansion rate is calculated: expansion rate = ((D2-D1) / D1)*100%; the deposition process recovery rate is calculated as follows: the mass of material added to the reaction zone is M1, the mass of material added to the collecting zone is M2, and the mass of material collected in the collecting zone after the deposition process is completed is M3, then: deposition process recovery rate = M3 / (M1+M2).
[0035] The test results are shown in Table 1.
[0036] Table 1: Test results of button cells made of silicon-based negative electrode materials in various embodiments and comparative examples
[0037] The Mg and Na content of the materials of each embodiment and comparative example was tested by inductively coupled plasma emission spectrometer (ICP), and the C content of the materials was tested by carbon sulfur analyzer. The specific sample test results are shown in Table 2.
[0038] Table 2: Elemental analysis and carbon content analysis results of silicon-based negative electrode materials of various embodiments and comparative examples
[0039] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.
[0040] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A silicon-based negative electrode material, characterized in that: It comprises a carbon matrix and a sodium-magnesium co-doped silicon oxide deposit filled in the pores of the carbon matrix; the silicon oxide deposit presents a core-shell structure, comprising a silicon oxide core uniformly doped with magnesium and a sodium-magnesium co-doped silicon oxide shell, and in the sodium-magnesium co-doped silicon oxide shell, the doping amount of sodium gradually decreases from the outside to the inside.
2. The silicon-based negative electrode material according to claim 1, characterized in that: The sodium-magnesium co-doped silicon oxide deposit accounts for 25% to 70% of the mass of the silicon-based negative electrode material; the doping amount of the magnesium element is 1% to 30% of the mass of the sodium-magnesium co-doped silicon oxide deposit, and the doping amount of the sodium element is 0.2% to 6.5% of the mass of the silicon-based negative electrode material.
3. The silicon-based negative electrode material according to claim 1, characterized in that: The silicon-based negative electrode material is coated with a carbon coating layer, and the thickness of the carbon coating layer is 1-150 nm.
4. The silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: The carbon matrix is porous carbon, the particle size D50 of the porous carbon is 1-25 μm, and the pore volume is 0.6-1.2 cm 3 / g, and the specific surface area is 1600~2200 m 2 / g.
5. A method for preparing the silicon-based negative electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing silicon powder, silicon dioxide powder and magnesium powder to obtain a mixed powder; (2) placing the mixed powder in a reaction zone of a vacuum sintering furnace, placing carbon powder in a receiving zone of the vacuum sintering furnace, and heating the vacuum sintering furnace to deposit the mixed powder in the carbon powder to obtain an intermediate product; (3) The intermediate product is mixed with sodium salt to obtain a mixture, the mixture is placed in a reaction furnace, and reacted at 550-1000° C. for 2-20 hours under a protective atmosphere, and then a carbon source gas is introduced to continue the reaction for 2-5 hours to obtain the silicon-based negative electrode material.
6. The method for preparing a silicon-based negative electrode material according to claim 5, characterized in that: In step (2), the mass ratio of the mixed powder to the carbon powder is 1:(0.4-3.0).
7. The method for preparing a silicon-based negative electrode material according to claim 5, characterized in that: In step (2), during the deposition process, the temperature of the reaction zone of the vacuum sintering furnace is controlled at 1300-1700°C, the temperature of the transition zone is controlled at 1200-1450°C, and the temperature of the receiving zone is controlled at 700-900°C.
8. The method for preparing a silicon-based negative electrode material according to claim 5, characterized in that: In step (2), the carbon powder is porous carbon, the particle size D50 of the porous carbon is 1-25 μm, and the pore volume is 0.6-1.2 cm 3 / g, with a specific surface area of 1600-2200 m 2 / g.
9. The method for preparing a silicon-based negative electrode material according to any one of claims 5 to 8, characterized in that: In step (1), the mass proportion of the magnesium powder in the mixed powder is 1% to 30%.
10. The method for preparing a silicon-based negative electrode material according to any one of claims 5 to 8, characterized in that: In step (1), the molar ratio of silicon powder to silicon dioxide is (0.8-1.15):
1.
11. The method for preparing a silicon-based negative electrode material according to any one of claims 5 to 8, characterized in that: In step (3), the mass proportion of the sodium salt in the mixture is 1% to 30%.
12. The method for preparing a silicon-based negative electrode material according to claim 11, characterized in that: In step (3), the sodium salt includes at least one of sodium carbonate, sodium bicarbonate and sodium acetate.
13. The method for preparing a silicon-based negative electrode material according to any one of claims 5 to 8, characterized in that: In step (3), the carbon source gas is acetylene, the protective atmosphere is a nitrogen atmosphere, and the mass flow ratio of the nitrogen to acetylene is 1:(1-0.25).
14. Use of the silicon-based negative electrode material according to any one of claims 1 to 4 or the silicon-based negative electrode material prepared by the preparation method according to any one of claims 5 to 13 in a lithium-ion battery.
Citation Information
Patent Citations
Silicon-based negative electrode material and preparation method thereof
CN115621433A
High-performance composite negative electrode material and preparation method and application thereof
CN118198291A
A silicon-based negative electrode material for a secondary battery, a method for preparing the same, and the secondary battery
CN111164803A
Negative electrode material containing metal-doped silicon-based composite material, preparation method and lithium battery
CN111554909A
Silicon-based composite, anode comprising same, and lithium secondary battery
CN112514116A